Exchange of Xcp (Gsp) Secretion Machineries between Pseudomonas aeruginosa and Pseudomonas alcaligenes: Species Specificity Unrelated to Substrate Recognition - de Groot, Arjan (American Society for Microbiology, 2001)
Pseudomonas aeruginosa and Pseudomonas alcaligenes are gram-negative bacteria that secrete proteins using the type II or general secretory pathway, which requires at least 12 xcp gene products (XcpA and XcpP to -Z). Despite strong conservation of this secretion pathway, gram-negative bacteria usually cannot secrete exoproteins from other species. Based on results obtained with Erwinia, it has been proposed that the XcpP and/or XcpQ homologs determine this secretion specificity (M. Linderberg, G. P. Salmond, and A. Collmer, Mol. Microbiol. 20:175–190, 1996). In the present study, we report that XcpP and XcpQ of P. alcaligenes could not substitute for their respective P. aeruginosa counterparts. However, these complementation failures could not be correlated to species-specific recognition of exoproteins, since these bacteria could secrete exoproteins of each other. Moreover, when P. alcaligenes xcpP and xcpQ were expressed simultaneously in a P. aeruginosa xcpPQ deletion mutant, complementation was observed, albeit only on agar plates and not in liquid cultures. After growth in liquid culture the heat-stable P. alcaligenes XcpQ multimers were not detected, whereas monomers were clearly visible. Together, our results indicate that the assembly of a functional Xcp machinery requires species-specific interactions between XcpP and XcpQ and between XcpP or XcpQ and another, as yet uncharacterized component(s).